Sitagliptin affects gastric cancer cells proliferation by suppressing Melanoma‐associated antigen‐A3 expression through Yes‐associated protein inactivation. (30th March 2020) - Wang, Qi; Lu, Pan; Wang, Tao; Zheng, Qianqian; Li, Yan; Leng, Sean X.; Meng, Xin; Wang, Biao; Xie, Jisheng; Zhang, Haiyan
Abstract: Sitagliptin is an emerging oral hypoglycemic agent that inhibits the development of a wide variety of tumors. Current researches indicate that the abnormal activation of Yes‐associated protein (YAP) promotes the proliferation and poor prognosis of multiple tumors. However, the ability of sitagliptin to regulate YAP and its effects on gastric cancer (GC) cells remain unclear. Here, we first showed that sitagliptin inhibited the proliferation of GC cells, and this inhibition was regulated by Hippo pathway. Sitagliptin phosphorylated YAP in a large tumor suppressor homolog‐dependent manner, thereby inhibiting YAP nuclear translocation, and promoted YAP cytoplasm retention. This inhibition can be blocked by adenosine 5′‐monophosphate‐activated protein kinase (AMPK). Moreover, sitagliptin could reduce the expression of tumor‐testis antigen Melanoma‐associated antigen‐A3 through YAP. In conclusion, sitagliptin may have a potential inhibitory effect on GC by AMPK/YAP/melanoma‐associated antigen‐A3 pathway. Abstract : Sitagliptin inhibits the proliferation and clonality of gastric cancer cells, which was accompanied by increased levels of adenosine 5′‐monophosphate‐activated protein kinase phosphorylation and Yes‐associated protein (YAP) phosphorylation expression and decreased YAP nuclear localization. In addition, sitagliptin reduces melanoma‐associated antigen‐A3 expression via the YAP pathway, which may improve the prognosis of gastric cancer.